Radiolarites and Radiolarian Cherts in Northern Croatia - Possible Sources for the Production of Artifacts - Halamić, Josip (Array, 2010)
Rhythmic bedding of alternating nonsiliceous and siliceous layers is one of the most prominent features of biogenic siliceous sediments. One of the best examples of rhythmites are Mesozoic ribbon radiolarites. In Northern Croatia, the deposits of radiolarian cherts and radiolarites, partially associated with magmatic rocks are located in county Banovina (Zrinska Mt), Žumberak, Medvednica, Ivanščica and Kalnik Mts. These rocks are constituents of Late Jurassic subduction complex (tectonic melánge). Palaeontological investigations revealed their Triassic (Ladinian-Carnian) and Jurassic (latest Bajocian-early Callovian) age. Macroscopical and microscopical examinations of samples reveal its low quality for stone tools production, but also its feasibility for local ad-hoc production. The radiolarites and radiolarian cherts near Lasinja in the northern Banovina are the possible sources for production of artifacts during (at least) the Lasinja culture period on wider territory of continental Croatia.